Talent Management and Employee Ambidexterity as the Key Success in the Industrial Revolution 4.0: an Empirical Study at Universitas Terbuka - Madurani, Dina Noval; Hadiwidjaja, Rini Dwiyani (Jurnal Ilmu Manajemen Profitability, 2025)
This study examines the impact of talent management on employee performance and employee ambidexterity at Universitas Terbuka. The research involved 164 respondents, consisting of lecturers and educational staff. The sample profile indicates that the majority of respondents are aged between 26 and 35, with 54% being female. Educational background data reveal that 69% hold a master’s degree, while 5% have a doctoral degree. The study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the validity, reliability, and structural relationships among variables. Convergent validity was evaluated using outer loading values and Average Variance Extracted (AVE), confirming that the indicators of talent management, employee ambidexterity, and employee performance meet the validity requirements. Discriminant validity was tested using the Fornell-Larcker criterion, ensuring that each construct is distinct from others. Reliability tests, measured through composite reliability and Cronbach’s Alpha, demonstrate that all constructs exhibit high internal consistency. The structural model analysis, including F-square, R-square, and adjusted R-square, shows that talent management significantly influences employee ambidexterity (R² = 0.622) and moderately affects employee performance (R² = 0.355). Path analysis using bootstrapping confirms the direct and indirect effects of talent management on employee ambidexterity and performance, highlighting the importance of talent management in enhancing workforce capabilities. This research provides valuable insights into human resource strategies within higher education institutions, emphasizing the role of effective talent management in improving employee adaptability and overall performance. Future studies should explore additional mediating factors to further understand the dynamics between talent management and organizational outcomes.